A Rare Case of Life-Threatening Invasive Mole - Shah, Rajiv; Samal, A.M. (Journal of Karnali Academy of Health Sciences, 2018)
A 23-year-old female with a known case of partial mole and under hCG follow up presented with acute abdominal pain and signs of hemoperitoneum. Emergency laparotomy revealed a molar pregnancy perforating through the uterine fundus, resulting in massive haemoperitoneum of 4 litres. Total abdominal hysterectomy was done. The serum β-hCG level regressed following hysterectomy.